ZAP-AIRTMMICRONIZER: IMPACT ON NEBULIZED SALBUTAMOL SULPHATE AND IPRATROPIUM BROMIDE PARTICLE SIZE - ZAMERY, MUHAMMAD IZZUDDIN; SAHUDIN, SHARIZA; RAHMAN, SHAHARIZUAN ABDUL; KOW, ALBERT (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to investigate the effect of the patented Zap-Air™ Micronizer on the particle size reduction of salbutamol sulphate (Ventolin), ipratropium bromide (Atrovent), and their combination (Combivent) nebulizing solutions. Methods: The study used an Omron Compressor Nebulizer NE-C28 and compressed oxygen at flow rates of 3L and 6L per minute. Particle size analysis was conducted using Malvern Spraytec Laser Diffraction System to measure DV4 (4% of particles in the sample), DV50 (50% of particles in the sample), DV90 (90% of particles in the sample). Drug deposition analysis was performed using the Next Generation Pharmaceutical Impactor (NGI) with High-Performance Liquid Chromatography (HPLC) to analyze the content at each stage. Results: The Zap-Air™ Micronizer effectively reduced the particle size of salbutamol sulphate and ipratropium bromide to less than 2 μm. Both Unit 1 and Unit 2 micronizers showed significant particle size reduction, with the average size of 50% of particles (DV50) being below 1 μm. Drug release intensity was significantly reduced when using the micronizers compared to the nebulizer alone. Conclusion: The Zap-Air™ Micronizer has the potential to enhance drug delivery and therapeutic effects in the treatment of Asthma and Chronic Obstructive Pulmonary Disease (COPD) by improving the deposition of salbutamol sulphate and ipratropium bromide into the smaller airways of the lungs.